Competency profiles for evidence-informed policy-making (EIPM): a rapid review - Barreto, Jorge Otávio Maia (2023)
Fundação Oswaldo Cruz. Fiocruz Brasília. Brasília, DF, Brasil / Hospital Sírio-Libanês. São Paulo, SP, Brazil.